PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF PADA MATA PELAJARAN DASAR-DASAR PROGRAM KEAHLIAN KELAS X DKV - Anisa, Rahmatin; Mulyono, Heri; Devegi, Mourend (Universitas Muhammadiyah Tapanuli Selatan, 2023)
The primary objective of this study is to develop interactive learning media for the subject of Basic Expertise in Class X DKV, utilizing the Adobe Animate application. This approach aims to ensure the validity and practicality of its implementation. The research methodology employed is Research and Development (RD), which follows the ADDIE model encompassing five essential phases: analysis, design, development, implementation, and evaluation.The validation results provided by media experts indicate a percentage of 86.57%, falling within the category of